2008
DOI: 10.1111/j.1365-2338.2008.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of weed hosts for Potato virus Y protection in Syria

Abstract: A survey of Potato virus Y (PVY) was carried out on weeds growing in and around potato fields in Syria during the autumn growing seasons of 2002, 2004 and 2006. A total of 59 samples of eight weed species and three tobacco (Nicotiana tabacum) samples were tested by ELISA using PVY antisera. Among them 15 samples belonged to Solanum nigrum (7 samples), Physalis sp. (6 samples) and tobacco (2 samples) were PVY infected. This suggests that weed hosts and neighbouring tobacco fields are natural reservoirs of PVY i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…In Europe, Kaliciak and Syller [40], reported other new wild hosts for PVY including Erodium cicutarium, Geranium pusillum, Lactuca serriola and Lamium purpureum. Chikh-Ali, et al [41], reported that PVY is very common in S. nigrum and Physalis spp. which are abundant at the ield margins in potato crops in Syria.…”
Section: Symptomatology and Host Range Of Potato Virus Y Potyvirusmentioning
confidence: 99%
“…In Europe, Kaliciak and Syller [40], reported other new wild hosts for PVY including Erodium cicutarium, Geranium pusillum, Lactuca serriola and Lamium purpureum. Chikh-Ali, et al [41], reported that PVY is very common in S. nigrum and Physalis spp. which are abundant at the ield margins in potato crops in Syria.…”
Section: Symptomatology and Host Range Of Potato Virus Y Potyvirusmentioning
confidence: 99%